Twilight Falls on Liberalism - Rudrangshu Mukherjee (New Delhi Aleph book company, 2018)
Recent political developments across large parts of the globe have made it clear that liberalism is in crisis. Several political regimes and political leaders have little time and respect for liberal values but it is important to understand that in many cases they have been empowered by popular social attitudes that have turned against liberalism. In order to understand this phenomenon, Rudrangshu Mukherjee goes back to the origins of liberalism to understand its substantive ideas and lineage. He shows how liberalism, a Western doctrine, flourished when Western empires dominated much of the world. Ironically, while values like freedom, democracy and citizenship were nurtured in the West, they were denied to the people of the countries that had been colonized by Western nations. Liberalism in the West thrived by being illiberal elsewhere. The contradictions within made liberalism vulnerable to attack. Totalitarian regimes swept it aside, and other doctrines replaced it with increasing frequency. In the twenty-first century, in both the East as well as the West, liberalism appears to be fast disappearing. This important book tells us why. (less)
Keywords: Liberalism